Complement C5a Alters the Membrane Potential of Neutrophils during Hemorrhagic Shock. (29th May 2018) - Messerer, David A. C.; Denk, Stephanie; Föhr, Karl J.; Halbgebauer, Rebecca; Braun, Christian K.; Hönes, Felix; Harant, Julia; Fauler, Michael; Frick, Manfred; Nußbaum, Benedikt L.; Radermacher, Peter; Hafner, Sebastian; et al.
Abstract : Background . Polymorphonuclear granulocytes (PMN) play a crucial role in host defense. Physiologically, exposure of PMN to the complement activation product C5a results in a protective response against pathogens, whereas in the case of systemic inflammation, excessive C5a substantially impairs neutrophil functions. To further elucidate the inability of PMN to properly respond to C5a, this study investigates the role of the cellular membrane potential of PMN in response to C5a. Methods . Electrophysiological changes in cellular and mitochondrial membrane potential and intracellular pH of PMN from human healthy volunteers were determined by flow cytometry after exposure to C5a. Furthermore, PMN from male Bretoncelles-Meishan-Willebrand cross-bred pigs before and three hours after severe hemorrhagic shock were analyzed for their electrophysiological response. Results . PMN showed a significant dose- and time-dependent depolarization in response to C5a with a strong response after one minute. The chemotactic peptide fMLP also evoked a significant shift in the membrane potential of PMN. Acidification of the cellular microenvironment significantly enhanced depolarization of PMN. In a clinically relevant model of porcine hemorrhagic shock, the C5a-induced changes in membrane potential of PMN were markedly diminished compared to healthy littermates. Overall, these membrane potential changes may contribute to PMN dysfunction in an inflammatory environment.